Ambulatory Sedation for Dental Procedures-Case of Cuenca, Ecuador - Eleonor María Velez-León; Karen Lozada Vargas; Katherine Cuenca-León; Cristina Acurio-Vargas; Adriana Zumba; Edisson-Mauricio P (MDPI AG, 2022)
In recent years, the dental treatment of children under sedation and/or general anesthesia on an outpatient basis has been developed as a behavioral management model in pediatric dentistry. The objective of this study was to establish the percentage of pediatric patients who required deep sedation on an outpatient basis in dental offices in the city of Cuenca, Ecuador. An observational study was conducted with a sample of 450 records of school- and preschool-age patients, where the variables were type and time of treatment, age, and sex. Statistical data were analyzed using the statistical program SPSS V.27 (IBM, Armonk, NY, USA). The highest percentage of children who received sedation were of preschool age. In general, there were three types of procedures per session, the most frequent being restorations (67%), followed by pulp treatment (49.8%) and, less frequently, minor surgery. The need for sedation for dental procedures is high in preschool patients, and ambulatory sedation has contributed to meeting this need. However, a regulation for its use is required at a national level.